IMPLIKASI HUKUM PEMBATASAN PERAN SERTA PEGAWAI NEGERI SIPIL DALAM PROSES POLITIK DI INDONESIA - Sudrajat, Tedi (Jurnal Dinamika Hukum, 2011)
In the form of philosophies, histories and comparative studies, limiting the political rights of civil Servant is a political outcome of the state to create a public official relations between the countries with the civil servant based on merit system that applies in the civil service law. The legal implications of the limiting the political rights of civil Servant which are : giving tribute, prohibition and administrative sanctions against the civil servant that involved in the process of politic in Indonesia.Key words : civil servant, political participation, political system